Capital account liberalisation in developing countries implications for South Africa - Feketha, Templeton Zolile (School of Economics, 2014)
The purpose of this dissertation is to access the desirability of controls on capital movements in South Africa. In line with the general international tendencies towards liberalisation, in recent years there has been increased pressure to lift exchange controls. Despite these pressures, some economists believe there is a need for the maintenance of controls. These arguments are based on issues relating to the inherent desirability of controls as well as the appropriate preconditions for liberalisation. The paper investigates the preconditions for capital account liberalisation, drawing on international experience, and considers whether or not they have been fulfilled in South Africa. In addition, the proper sequencing of capital opening itself is examined. A literature survey is the main research method used, utilising the literature on financial reforms of some less developed countries. The countries of the Southern Cone of Latin America (Argentina, Chile and Uruguay) are used to illustrate examples of failed experiences. In the light of the lessons learned from the above, the major results are that (1) South Africa's capital controls should be abolished, although gradually; (2) macroeconomic stability is the key to successful liberalisation; and (3) a fairly liberal domestic financial system is a prerequisite for external liberalisation.